Sampling and purification methods for dating by atom trap trace analysis in various environmental applications - Arck, Yannis; Meienburg, Florian; Wachs, David; Beyersdorfer, Stefan; Kersting, Arne; Schmidt, Maximilian; Oberthaler, Markus K.; Aeschbach, Werner (ACS earth and space chemistry, 2025)
Atom Trap Trace Analysis (ATTA) has enabled new applications of the noble gas radioisotopes 39Ar, 81Kr, and 85Kr for dating environmental processes in a broad range of environmental systems on time scales of years to about 1 Myr. Compared to low-level counting of 39Ar and 85Kr, ATTA has reduced sample size requirements from over 1000 to a few liters of water. The scope of possible applications has widened from groundwater systems to the global ocean, stratified lakes, alpine glaciers, and ice deposits, or even nonhydrological systems like permafrost and rocks. New applications and sample types require appropriate sampling and preparation procedures, presented herein with a focus on 39Ar applications in ocean water, lake water, and glacier ice. Water (or gas) samples with volumes around 10 L can be collected, transported, and stored in commercial propane gas bottles. Blocks or drill cores of ice must be transported frozen, transferred into suitable vacuum containers, evacuated, and then melted to release trapped gases. A dedicated sample preparation line extracts all gases from the sample containers. After removing water vapor the remaining gases are collected on a cooled activated charcoal trap. Thereafter, the gas mixture passes two titanium sponge getters at different temperatures to absorb all reactive gases, leaving only the purified inert noble gases with a dominating argon fraction. An additional gas-chromatographic separation of krypton from argon is possible if required. The presence of vast amounts of gases may necessitate sophisticated sampling methods and modifications to the preparation process to remove the undesired bulk gases before the standardized purification to protect the getters. Important purification parameters of selected samples from field campaigns are presented as examples for different environmental compartments, including groundwater, ocean water, extremely gas-rich lake water, and glacier ice.
Online veröffentlicht: 3. Juli 2025
Gesehen am 30.10.2025